A rare cause of small bowel obstruction - Elif Peker; Ayşe Erden; İlhan Erden; Murat Törüner (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Peker E, Erden A, Erden İ, Törüner M. A rare cause of small bowel obstruction. Turk J Gastroenterol 2018; 29: 237-8.